Dynamics of forward and backward translocation of mRNA in the ribosome. - Ping Xie (PLoS ONE, 2013)
Translocation of the mRNA-tRNA complex in the ribosome, which is catalyzed by elongation factor EF-G, is one of critical steps in the elongation cycle of protein synthesis. Besides this conventional forward translocation, the backward translocation can also occur, which can be catalyzed by elongation factor LepA. However, the molecular mechanism of the translocation remains elusive. To understand the mechanism, here we study theoretically the dynamics of the forward translocation under various nucleotide states of EF-G and the backward translocation in the absence of and in the presence of LepA. We present a consistent explanation of spontaneous forward translocations in the absence of EF-G, the EF-G-catalyzed forward translocations in the presence of a non-hydrolysable GTP analogue and in the presence of GTP, and the spontaneous and LepA-catalyzed backward translocation. The theoretical results provide quantitative explanations of a lot of different, independent experimental data, and also provide testable predictions.